1993
DOI: 10.1111/j.1749-6632.1993.tb23054.x
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule‐associated Protein Tau, Paired Helical Filaments, and Phosphorylationa

Abstract: This paper summarizes our recent studies on microtubule-associated protein tau and its pathological state resembling that of the paired helical filaments of Alzheimer's disease. The Alzheimer-like state of tau protein can be identified and analyzed in terms of certain phosphorylation sites and phosphorylation-dependent antibody epitopes. It can be induced by protein kinases which tend to phosphorylate serine or threonine residues followed by a proline; this includes mitogen-activated protein kinase (MAPK) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 18 publications
(1 reference statement)
0
24
0
1
Order By: Relevance
“…Interestingly, the neuroprotective effect of FZS is superior to that of roscovitine or calpeptin. It is most likely that FZS is a herbal medicine that contains multiple components, and we consider that in addition to the inhibition of Cdk5 activity, other tau kinase such as GSK3b may also be involved [11]. However, this will be further explored in future studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, the neuroprotective effect of FZS is superior to that of roscovitine or calpeptin. It is most likely that FZS is a herbal medicine that contains multiple components, and we consider that in addition to the inhibition of Cdk5 activity, other tau kinase such as GSK3b may also be involved [11]. However, this will be further explored in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…Given the evidence that Ab requires tau proteins to induce its neurotoxicity [9], and tau phosphorylation is a limiting factor in Ab-induced cell death [10], it is reasonable to speculate that Ab-induced tau phosphorylation may be an important pathogenesis of AD [4]. Earlier studies have indicated that Ab-induced tau phosphorylation is mediated by the activation of various kinases including glycogen synthase kinase 3 beta (GSK3b), mitogen-activated protein (MAP) kinase, and cyclin-dependent kinase 5 (Cdk5) [11][12][13][14]. Of these kinases, Cdk5 has been found to phosphorylate tau at AD-specific phospho-epitopes and its activity is enhanced in response to Ab in cultured neurons [13,15,16].…”
Section: Introductionmentioning
confidence: 98%
“…Recombinant tau is a good substrate for GSK3␤ in vitro (21,38,39) and is unprimed. When GSK3␤ was immunoprecipitated from cell lysates that were transfected with GSK3␤ and FRAT-2 with a monoclonal HA antibody, it phosphorylated the recombinant tau to the same extent as the GSK3␤ immunoprecipitated from cells expressing just GSK3␤ (Fig.…”
Section: Frat-2 Does Not Significantly Affect Gsk3␤ Phosphorylation Omentioning
confidence: 99%
“…Tau is an excellent substrate for GSK3b (Mandelkow et al 1993;Lovestone et al 1994;Wagner et al 1996). To further examine the effects of axin on GSK3b-mediated tau phosphorylation, HEK cells were transfected as above and GSK3b was immunoprecipitated from the lysates and used to [ 32 P]phosphorylate recombinant tau, in an in vitro assay (Fig.…”
Section: Axin Decreases the Phosphorylation Of Recombinant Tau In Vitromentioning
confidence: 99%